2020
DOI: 10.3899/jrheum.200435
|View full text |Cite
|
Sign up to set email alerts
|

Higher Prevalence and Degree of Insulin Resistance in Patients With Rheumatoid Arthritis Than in Patients With Systemic Lupus Erythematosus

Abstract: Objective Since insulin resistance (IR) is highly prevalent in patients with systemic lupus erythematosus (SLE) and rheumatoid arthritis (RA), we aimed to determine whether differences in IR between the two conditions exist. Methods Cross-sectional study that encompassed 413 non-diabetic subjects, 186 SLE and 227 RA. Glucose, insulin and C-peptide serum levels, as well as IR by the homeostatic model assessment (HOMA2) were studied. A multivariable regression analysis was performed to evaluate the differences i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 31 publications
0
7
0
2
Order By: Relevance
“…In SLE patients, the Quantose algorithm for IR correlated with other IR surrogates and levels of complement C. However, no other associa tions between the Quantose IR score (or its metabolites) and SLE disease indicators, including vitamin D levels were identified. Several studies have determined the prevalence of IR in patients with SLE, finding a range of 14 % to 48 %, and compared it with that of controls [24][25][26][27]. Most of these analyses were performed using the HOMA model; in our study, the prevalence of IR was 39.1 % and 42.2 % using HOMA1IR and HOMA2IR, respectively.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…In SLE patients, the Quantose algorithm for IR correlated with other IR surrogates and levels of complement C. However, no other associa tions between the Quantose IR score (or its metabolites) and SLE disease indicators, including vitamin D levels were identified. Several studies have determined the prevalence of IR in patients with SLE, finding a range of 14 % to 48 %, and compared it with that of controls [24][25][26][27]. Most of these analyses were performed using the HOMA model; in our study, the prevalence of IR was 39.1 % and 42.2 % using HOMA1IR and HOMA2IR, respectively.…”
Section: Discussionmentioning
confidence: 67%
“…Several studies have determined the prevalence of IR in patients with SLE, finding a range of 14% to 48%, and compared it with that of controls 24 25 26 27 . Most of these analyses were performed using the HOMA model; in our study, the prevalence of IR was 39.1% and 42.2% using HOMA1-IR and HOMA2-IR, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Избыточный вес и ожирение являются факторами риска ИР и МС. Частота ИР у больных СКВ составляет 14-49,1% [18][19][20][21][22][23], МС -3,3-45,2% [24], а ожирения -28-50% [2][3][4].…”
Section: Discussionunclassified
“…Rheumatoid arthritis (RA) is a systemic autoimmune disease associated with a high prevalence of insulin resistance [ 1 , 2 ], a known risk factor for cardiovascular disease and type 2 diabetes [ 3 ]. Several studies have reported that insulin resistance in RA is associated with systemic inflammation, rheumatoid factor and anti-citrullinated protein antibodies (ACPA) seropositivity, obesity, and glucocorticoid use [ 4 – 6 ].…”
Section: Introductionmentioning
confidence: 99%